CHLORINE DEMAND AND BACTERIAL ABUNDANCE OF SHRIMP POND WATER UNDER DIFFERENT SUSPENDED SOLID CONCENTRATIONS - Husnah Husnah (Indonesian Fisheries Research Journal, 2001)
An experiment has been conducted to evaluate the chlorine demand and efficacy of 6 chlorine concentrations in brackish pond water, to control indigenous bacteria in shrimps pond.